Pengaruh sistem kebijakan tunjangan kinerja terhadap kinerja pegawai pada Direktorat Jenderal Perimbangan Keuangan - Alin Tamanna Rahmani; Sulaeman Sulaeman (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2022)
This research has purposes to collect information and analyze the effect of performance-based allowance policy system on the employee’s performance in Directorate General of Fiscal Balance. This research sample consists of a number of staff employees which is categorized based on the job rank by using stratified random sampling method and Cohen’s approach. This research data is collected from a perception survey related to the implementation of performance-based allowance policy system which consists of three aspects, including the Presidential Decree of 156 /2014, the Minister of Finance Regulation of 93/PMK.01/2018 juncto 85/PMK.01/2015 junctis 214/PMK.01/2011, and the Minister of Finance Regulation of 176/PMK.01/2018. This research uses formative evaluation method and descriptive analysis technique by Partial Least Square (PLS) approach according to Chin’s criterion. The final conclusion is that performance-based allowance policy system has positive and significant effect on the employee’s performance in Directorate General of Fiscal Balance.